A test for paedomorphism in domestic pig cranial morphology. (31st August 2017) - Evin, Allowen; Owen, Joseph; Larson, Greger; Debiais-Thibaud, Mélanie; Cucchi, Thomas; Vidarsdottir, Una Strand; Dobney, Keith
Abstract : Domestic animals are often described as paedomorphic, meaning that they retain juvenile characteristics into adulthood. Through a three-dimensional landmark-based geometric morphometric analysis of cranial morphology at three growth stages, we demonstrate that wild boar ( n = 138) and domestic pigs ( n = 106) ( Sus scrofa ) follow distinct ontogenetic trajectories. With the exception of the size ratio between facial and neurocranial regions, paedomorphism does not appear to be the primary pattern describing the observed differences between wild and domestic pig cranial morphologies. The cranial phenotype of domestic pigs instead involves developmental innovation during domestication. This result questions the long-standing assumption that domestic animal phenotypes are paedomorphic forms of their wild counterparts.